2017
DOI: 10.18632/oncotarget.20764
|View full text |Cite
|
Sign up to set email alerts
|

Subependymal giant cell astrocytomas in Tuberous Sclerosis Complex have consistent TSC1/TSC2 biallelic inactivation, and no BRAF mutations

Abstract: Subependymal giant cell astrocytomas (SEGAs) are rare, low-grade glioneuronal brain tumors that occur almost exclusively in patients with tuberous sclerosis complex (TSC). Though histologically benign, SEGAs can lead to serious neurological complications, including hydrocephalus, intractable seizures and death. Previous studies in a limited number of SEGAs have provided evidence for a biallelic two-hit inactivation of either TSC1 or TSC2, resulting in constitutive activation of the mechanistic target of rapamy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 55 publications
3
47
0
Order By: Relevance
“…A second somatic event is required for hamartoma formation. In accordance with this model, loss of heterozygosity and small changes on the second allele have been found in renal angiomyolipomas, some cells in cortical tubers and subependymal giant cell astrocytomas (SEGAs) (Au, Hebert, Roach, & Northrup, 1999;Bongaarts et al, 2017). Recently, several studies demonstrated that biallelic loss (either second-hit point mutations or copy-neutral LOH) of TSC1/TSC2 is the primary driver event for angiomyolipoma development, and somatic mutations in other known cancer-associated genes are very rare (Giannikou et al, 2016).…”
Section: Development Of Hamartomas In Tsc Follows Knudson's Two-hitmentioning
confidence: 73%
See 1 more Smart Citation
“…A second somatic event is required for hamartoma formation. In accordance with this model, loss of heterozygosity and small changes on the second allele have been found in renal angiomyolipomas, some cells in cortical tubers and subependymal giant cell astrocytomas (SEGAs) (Au, Hebert, Roach, & Northrup, 1999;Bongaarts et al, 2017). Recently, several studies demonstrated that biallelic loss (either second-hit point mutations or copy-neutral LOH) of TSC1/TSC2 is the primary driver event for angiomyolipoma development, and somatic mutations in other known cancer-associated genes are very rare (Giannikou et al, 2016).…”
Section: Development Of Hamartomas In Tsc Follows Knudson's Two-hitmentioning
confidence: 73%
“…In accordance with this model, loss of heterozygosity and small changes on the second allele have been found in renal angiomyolipomas, some cells in cortical tubers and subependymal giant cell astrocytomas (SEGAs) (Au, Hebert, Roach, & Northrup, 1999;Bongaarts et al, 2017). Germline pathogenic variants in TSC1 or TSC2 alone are not sufficient to cause the tumors.…”
Section: Pathogenesis: the Mtor Pathwaymentioning
confidence: 74%
“…It is intriguing that mutant pericytes that likely give rise to the TSC-associated renal angiomyolipoma (Siroky et al 2014) could also be involved in TSC renal cystogenesis. Pericytes that have lost TSC gene function may be responsible for altered blood brain barrier function giving rise to the tensor weighted imaging findings in TSC (Jurkiewicz et al 2007;Arulrajah et al 2009;Ertan et al 2010) and may participate in inducing subependymal giant cell astrocytoma formation, a TSC tumor also sometimes identified without loss of heterozygosity (Parry et al 2000;Bongaarts et al 2017;Roux et al 2017), possibly through this extracellular vesicle mechanism. The expansion of A-intercalated cell as well as potential role for extracellular vesicles in many aspects of TSC renal cystic disease manifestation offers new therapeutic opportunities for intervention in this disease.…”
Section: Discussionmentioning
confidence: 99%
“…12 Furthermore, some patients developed only one TSC-associated manifestation, that is, sporadic SEGA or sporadic lymphangiomyomatosis. 4,13,14 Somatic TSC1/TSC2 variants were detected in some but not all of these cases.…”
Section: Subependymal Giant Cell Astrocytoma Harboring a Prrc2b-alk Fmentioning
confidence: 96%
“…Martin et al reported that somatic or germline TSC1/TSC2 variants were not detected in two out of 66 patients with TSC when using whole‐exome sequencing, single‐nucleotide polymorphism arrays, and targeted deep sequencing . Furthermore, some patients developed only one TSC‐associated manifestation, that is, sporadic SEGA or sporadic lymphangiomyomatosis . Somatic TSC1/TSC2 variants were detected in some but not all of these cases.…”
mentioning
confidence: 99%